Analisis Kemampuan Penulisan Tanda Baca, Huruf Kapital dan Kalimat dalam Karangan Deskripsi Siswa Kelas VII SMPN 10 Kota Jambi - Kore, Kristina Leoni; Rasdawita, Rasdawita; Harahap, Eddy Pahar; Akhyarruddin, Akhyarruddin (Universitas Batanghari Jambi, 2024)
Writing an essay is a skill that a person has because an essay is a work that describes a situation with writing that can be read but the reader is also invited to feel and imagine the situation in the essay. In learning Indonesian, essays are very important to learn because they can create a work. which provides knowledge, ideas and pleasure for the writer. Writing descriptions is an important thing to explain the situation and place in an essay but students often make writing errors, these errors occur because students do not understand punctuation, capital letters and the correct sentences to use in writing. This research aims to analyze and describe punctuation errors in students' descriptive essay writing. The method used in research is the description method. The researcher chose the description method with the aim of explaining the circumstances and conditions of the data systematically and factually. This research approach uses a quantitative approach because this research produces data in the form of numbers from the assessment of students' abilities in writing punctuation marks, capital letters and sentences in descriptive essays. from the results of the research explained in chapter IV, it can be concluded that the ability to write punctuation, capital letters, sentences for class VII E of SMP Negeri 10 Jambi City for the 2023/2024 academic year is capable with a score of 77. In writing punctuation, capital letters, sentences in The descriptive essay of class VII B students of SMP Negeri 10 Jambi City for the 2023/2024 academic year is very capable with an assessment of 82.